The Impact of Corporate ESG Performance on Debt Financing Costs - Wu, Yizhou (Transactions on Economics, Business and Management Research, 2024)
Guided by China’s sustainable development philosophy of innovation, coordination, green development, openness, and shared prosperity, as well as the ’dual carbon’ goals, ESG performance has gradually become an important metric for corporate sustainable development. This paper selects A-share listed companies from 2012 to 2022 as the research objects, and explores the impact of corporate ESG performance on their debt financing costs. The research results show that corporate ESG performance has an inverse impact on their debt financing costs, and further mechanism testing reveals that the risk level and financing constraint costs of enterprises both have a positive moderating effect on this impact. Heterogeneity tests indicate that the inverse impact of corporate ESG performance on debt financing costs is more pronounced in western enterprises and enterprises where the chairperson and general manager are separated.